Ruminal microbiome–host metabolome crosstalk in the synthesis of unsaturated fatty acids in buffalo milk - Ye Yu; Runqi Fu; Chunjia Jin; Huan Gao; Lin Han; Min Qi; Binlong Fu; Qian Li; Yuyan Wang; Yanfen Cheng; Jing Leng (Journal of Dairy Science, 2025)
ABSTRACT: Interactions between rumen microorganisms and their metabolites contribute to milk yield and milk fat content in dairy cows. However, whether rumen microbes and host metabolism affect fatty acid synthesis in milk is unknown. In this study, we investigated the potential regulatory mechanisms affecting the UFA content of Binglangjiang buffalo by using macrogenomics and metabolomics. Macrogenomic analysis showed that Bacteroides was significantly more abundant in the high UFA group (HF), contributing to the improvement of functions related to fatty acid synthesis. Then, we found that the rumen microbiota of the HF group was enriched in 2 important pathways involved in lipid metabolism (i.e., fatty acid biosynthesis and fatty acid metabolism), suggesting that more fatty acids were synthesized in the HF group. Metabolomics analyses showed that most of the UFA were more abundant in the HF group, which was also confirmed by the quantification of related metabolic pathways in milk fatty acids, suggesting that the HF group has a higher capacity to synthesize MUFA and PUFA. Correlation analysis of rumen lipid metabolic pathways and metabolites revealed that metabolic pathways such as fatty acid biosynthesis, fatty acid metabolism, metabolic pathways, and peroxisome proliferator-activated receptor (PPAR) signaling pathway, which were significantly enriched in the HF group compared with the low UFA group, were significantly and positively correlated with multiple UFA . The synthesis of UFA is mainly influenced by Bacteroides, Prevotella, and Bacteroidaceae, and regulated by fatty acid biosynthesis, fatty acid metabolism, and PPAR signaling pathways, which together influence the synthesis of UFA in buffaloes.